Viability and Stress Response of Putative Probiotic Lactobacillus plantarum Strains in Honey Environment - Bemmo Kamdem Ulrich Landry; Zambou Ngoufack François; Rui-Yan Wang; Zhu Taicheng; Yin Li (Probiotics and Antimicrobial Proteins, 2018)

Iron plaque formation on wetland-plant roots accelerates removal of water-borne antibiotics - Yiping Tai; Nora Fung-Yee Tam; Rui Wang; Yang Yang; Jianhua Lin; Jiaxi Wang; Yufen Yang; Li Li; Yaoming Sun (Plant and Soil, 2018)

Plant organic N uptake maintains species dominance under long-term warming - Lili Jiang; Shiping Wang; Pang Zhe; Xingliang Xu; Paul Kardol; Yaoming Li; Lirong Zhang; Yanfen Wang; Zhong Lei; Zhichun Lan; Paul W. Hill; Zhenhua Zhang; et al. (Plant and Soil, 2018)

Laminar Distribution of Neurochemically-Identified Interneurons and Cellular Co-expression of Molecular Markers in Epileptic Human Cortex - Qiyu Zhu; Wei Ke; Quansheng He; Xiongfei Wang; Rui Zheng; Tianfu Li; Guoming Luan; Yue-Sheng Long; Wei-Ping Liao; Yousheng Shu (Neuroscience Bulletin, 2018)

Curcumin confers hepatoprotection against AFB1-induced toxicity via activating autophagy and ameliorating inflammation involving Nrf2/HO-1 signaling pathway - Ishfaq Muhammad; Xinghe Wang; Sihong Li; Rui Li; Xiuying Zhang (Molecular Biology Reports, 2018)

Analysis of the triggering conditions and erosion of a runoff-triggered debris flow in Miyun County, Beijing, China - Chao Ma; Jiayong Deng; Rui Wang (Landslides, 2018)

Comparative study on mitogenomes of green tide algae - Chuner Cai; Feng Liu; Ting Jiang; Lingke Wang; Rui Jia; Lingjie Zhou; Kai Gu; Jianfeng Ren; Peimin He (Genetica, 2018)

Spermidine application alleviates salinity damage to antioxidant enzyme activity and gene expression in alfalfa - Yanhong Lou; Rui Guan; Mingjie Sun; Fei Han; Wei He; Hui Wang; Fupeng Song; Xiumin Cui; Yuping Zhuge (Ecotoxicology, 2018)

Genome-Wide Identification of Circular RNAs in Fungal Parasite Nosema ceranae - Rui Guo; Dafu Chen; Huazhi Chen; Cuiling Xiong; Yanzhen Zheng; Chunsheng Hou; Yu Du; Sihai Geng; Haipeng Wang; Zhou Dingding; Guo Yilong (Current Microbiology, 2018)

MiR-429 improved the hypoxia tolerance of human amniotic cells by targeting HIF-1α - Lihao Ge; Yuyan Wang; Yang Cao; Gang Li; Rui Sun; Peng Teng; Yansong Wang; Yunlong Bi; Zhanpeng Guo; Yajiang Yuan; Deshui Yu (Biotechnology Letters, 2018)

Functional brain abnormalities in major depressive disorder using the Hilbert-Huang transform - Haibin Yu; Feng Li; Tong Wu; Rui Li; Li Yao; Chuanyue Wang; Xia Wu (Brain Imaging and Behavior, 2018)

Characterization of the complete chloroplast genomes of three Chirita species (C. brachytricha, C. eburnea & C. liboensis) endemic to China - Na Hou; Gang Wang; Cong-Rui Li; Yang Luo (Conservation Genetics Resources, 2018)

Characterization and phylogenetic analysis of the complete maternal mitochondrial genome of freshwater mussel Aculamprotula scripta (Bivalvia: Unionidae: Unioninae) - Rui-Wen Wu; Sa Wang; Yi-Tong Liu; Xiong-Jun Liu; Chun-Hua Zhou; Shan Ouyang; Xiao-Ping Wu (Conservation Genetics Resources, 2018)

Identification of the complete mitochondrial genome of Garra pingi pingi (Cypriniformes, Cyprinidae) - Yuan-Chao Zou; Mei Chen; Chuan-Jie Qin; Yong-Ming Wang; Rui Li; Ze-Min Qi; Zheng-Yong Wen (Conservation Genetics Resources, 2018)

The complete mitochondrial genome of the hybrid of Acipenser dabryanus (♀) × A. schrenckii (♂) and its phylogeny - Yuanchao Zou; Junying Zhang; Zhengyong Wen; Chuanjie Qin; Yongming Wang; Rui Li; Zemin Qi (Conservation Genetics Resources, 2018)

Direct and legacy effects of herbivory on growth and physiology of a clonal plant - Bi-Cheng Dong; Mo-Zhu Wang; Rui-Hua Liu; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Biological Invasions, 2018)

Complete nucleotide sequence of a novel monopartite begomovirus infecting Ageratum conyzoides in China - Pengbai Li; Chenchen Jing; Rui Wang; Jiang Du; Gentu Wu; Mingjun Li; Xianchao Sun; Ling Qing (Archives of Virology, 2018)

Assessing spectral indices to estimate the fraction of photosynthetically active radiation absorbed by the vegetation canopy - Dailiang Peng; Helin Zhang; Le Yu; Mingquan Wu; Fumin Wang; Wenjiang Huang; Liangyun Liu; Rui Sun; Cunjun Li; Dacheng Wang; Fubao Xu (International Journal of Remote Sensing, 2018)

Morphology and molecular phylogeny of two new species of Spirostrombidium (Ciliophora, Oligotrichia), with a key to the species of Spirostrombidium - Rui Wang; Wen Song; Zhenzhen Yi; Khaled A. S. Al-Rasheid; Xiaozhong Hu (Systematics and Biodiversity, 2018)

A new isoflavanone from Ficus tikoua Bur - Si-Yu Zhou; Rui Wang; Li-Qing Deng; Xiao-Long Zhang; Min Chen (Natural Product Research, 2018)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

Spatial patterns of interprovincial mountain geographical names in China and implications for regional governance - Sheng-rui Zhang; Ying-jie Wang; Hong-run Ju; Tong-yan Zhang; Dai-chao Li; Lei Fang; Ying-ying Wang (Journal of Mountain Science, 2018)

Utilizing skew normal distribution to unmix grain-size distribution of swampy lakeshore: example from Lake Ulungur, China - Rui Yuan; Changmin Zhang; Xulong Wang; Rui Zhu (Arabian Journal of Geosciences, 2018)

Interactions Between Biological Products and Product Packaging and Potential Approaches to Overcome Them - Minjia Wang; Yusheng Li; Priyanka Srinivasan; Zhiqing Hu; Rui Wang; Anggrida Saragih; M. A. Repka; S. N. Murthy (AAPS PharmSciTech, 2018)

Role of clouds in accelerating cold‐season warming during 2000–2015 over the Tibetan Plateau - Shan Hua; Yuzhi Liu; Rui Jia; Shuting Chang; Chuqiao Wu; Qingzhe Zhu; Tianbin Shao; Bing Wang (International Journal of Climatology, 2018)
With the global warming slowdown in the twenty‐first century, a huge discrepancy in regional climate warming has been identified over the main region of the Tibetan Plateau (TP). Compared with the +0.04 °C/decade warming from 1961 to 1999, the warming greatly accelerated for the period 2000–2015 at a rate of +0.30 °C/decade. During the same period, warming in the cold season (November to March) was more pronounced than in the warm season (May to September) over the TP. The results also indicated that the middle‐level cloud (middle cloud) decreased (−0.359%/year), while the high‐level cloud (high cloud) increased (+0.241%/year) over almost all the TP during the cold season. Further analysis showed positive net cloud radiative forcing over the western TP from 2000–2015, that is, a heating effect of clouds, especially in the cold season. Combining the trends of the increase in high cloud and the decrease in middle cloud over most parts of the TP, the decreased albedo effect of middle cloud and the increased longwave greenhouse effect of high cloud may have partially contributed to the sustained warming, especially in the cold season from 2000 to 2015. Meanwhile, the results showed that the warming rate and cloud area fraction changes were significantly amplified with elevation. The analysis based on a model of Coupled Model Intercomparison Project Phase 5 shows that the decreased middle cloud plays more important role than the increased high cloud in modulating the enhanced warming over the TP, especially in the cold season.

An assessment of air-quality monitoring station locations based on satellite observations - Tao Yu; Wen Wang; Pubu Ciren; Rui Sun (International Journal of Remote Sensing, 2018)

Acupuncture Prevents the Impairment of Hippocampal LTP Through β1-AR in Vascular Dementia Rats - Ling-Yong Xiao; Xue-Rui Wang; Jing-Wen Yang; Yang Ye; Wen Zhu; Yan Cao; Si-Ming Ma; Cun-Zhi Liu (Molecular Neurobiology, 2018)

Numerical Analysis of Air Leakage Characteristics of Coal Seam Goaf Close to Thin Band - Mingguang Zhang; Peipeng Zhang; Rui Wang; Huining Chen; Peng Kong (Geotechnical and Geological Engineering, 2018)

A simplified method for analyzing the fundamental frequency of monopile supported offshore wind turbine system design - Chunbao Yang; Rui Wang; Jianmin Zhang (Earthquake Engineering and Engineering Vibration, 2018)

Spatial Distribution and Risk Assessment of Heavy Metals in Paddy Soils of Yongshuyu Irrigation Area from Songhua River Basin, Northeast China - Zhengwu Cui; Yang Wang; Na Zhao; Rui Yu; Guanghui Xu; Yong Yu (Chinese Geographical Science, 2018)

2,4-Dimethylaniline generates phosphorylated histone H2AX in human urothelial and hepatic cells through reactive oxygen species produced by cytochrome P450 2E1 - Yonggang Qi; Tatsushi Toyooka; Hiroki Kashiwagi; Yukie Yanagiba; Shigeki Koda; Hisayoshi Ohta; Rui-Sheng Wang (Archives of Toxicology, 2018)

The role of autophagy in pulmonary hypertension: a double-edge sword - Rui Chen; Meiping Jiang; Bo Li; Wei Zhong; Zhongqun Wang; Wei Yuan; Jinchuan Yan (Apoptosis, 2018)

Lappaconitine, a C18-diterpenoid alkaloid, exhibits antihypersensitivity in chronic pain through stimulation of spinal dynorphin A expression - Ming-Li Sun; Jun-Ping Ao; Yi-Rui Wang; Qian Huang; Teng-Fei Li; Xin-Yan Li; Yong-Xiang Wang (Psychopharmacology, 2018)

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

Biglycan, a Nitric Oxide-Downregulated Proteoglycan, Prevents Nitric Oxide-Induced Neuronal Cell Apoptosis via Targeting Erk1/2 and p38 Signaling Pathways - Sujuan Chen; Dandan Guo; Wei Zhang; Yunfei Xie; Haijie Yang; Binfeng Cheng; Lei Wang; Rui Yang; Jiajia Bi; Zhiwei Feng (Journal of Molecular Neuroscience, 2018)

Alzheimer’s Disease Risk Variant rs2373115 Regulates GAB2 and NARS2 Expression in Human Brain Tissues - Guiyou Liu; Tao Wang; Rui Tian; Yang Hu; Zhifa Han; Pingping Wang; Wenyang Zhou; Peng Ren; Jian Zong; Shuilin Jin; Qinghua Jiang (Journal of Molecular Neuroscience, 2018)

Increasing grassland degradation stimulates the non-growing season CO2 emissions from an alpine meadow on the Qinghai–Tibetan Plateau - Lei Ma; Zhisheng Yao; Xunhua Zheng; Han Zhang; Kai Wang; Bo Zhu; Rui Wang; Wei Zhang; Chunyan Liu (Environmental Science and Pollution Research, 2018)

Precipitation characteristics over the steep slope of the Himalayas in rainy season observed by TRMM PR and VIRS - Yunfei Fu; Xiao Pan; Tao Xian; Guosheng Liu; Lei Zhong; Qi Liu; Rui Li; Yu Wang; Ming Ma (Climate Dynamics, 2018)

Health Risk Assessment for Local Residents from the South China Sea Based on Mercury Concentrations in Marine Fish - Shao-wei Chen; Zi-hui Chen; Ping Wang; Rui Huang; Wei-lun Huo; Wei-xiong Huang; Xing-fen Yang; Jie-wen Peng (Bulletin of Environmental Contamination and Toxicology, 2018)

Anemia and Iron Status Among Different Body Size Phenotypes in Chinese Adult Population: a Nation-Wide, Health and Nutrition Survey - Jiang Li; Cheng Xiao; Hui Yang; Yun Zhou; Rui Wang; Yongtong Cao (Biological Trace Element Research, 2018)

The effects of codon usage on the formation of secondary structures of nucleocapsid protein of peste des petits ruminants virus - Xiao-xia Ma; Yi-ning Wang; Xiao-an Cao; Xue-rui Li; Yong-sheng Liu; Jian-hua Zhou; Xue-peng Cai (Genes & Genomics, 2018)

Recent Developments in Commercial Processes for Refining Bio-Feedstocks to Renewable Diesel - Bo Zhang; Jinsheng Wu; Changyan Yang; Qi Qiu; Qiangu Yan; Rui Li; Baowei Wang; Jinlong Wu; Yigang Ding (BioEnergy Research, 2018)

Three-dimensional numerical modeling of gravity anomalies based on Poisson equation in space-wavenumber mixed domain - Shi-Kun Dai; Dong-Dong Zhao; Qian-Jiang Zhang; Kun Li; Qing-Rui Chen; Xu-Long Wang (Applied Geophysics, 2018)

Paleoenvironmental implications of the calcium isotope characteristics in the MD81349 from the Nintyeast Ridge in the Indian Ocean - Feng Wang; Nianqiao Fang; Chaoyong Hu; Sarah Goldsmith; Yonghang Xu; Xuan Ding; Aijun Wang; Ping Chen; Rui Bao (Acta Oceanologica Sinica, 2018)

Characterization of clinical features and outcome for human-to-human transmitted severe fever with thrombocytopenia syndrome - Bei Jia; Weihua Wu; Rui Huang; Guiyang Wang; Peixin Song; Yang Li; Yong Liu; Yali Xiong; Xiaomin Yan; Yingying Hao; Juan Xia; Zhaoping Zhang; et al. (Infectious Diseases, 2018)

Development of Ultra-sensitive Method for Determination of Trace Atrazine Herbicide in Environmental Water Using Magnetic Graphene Oxide-Based Solid-Phase Extraction Coupled with Dispersive Liquid-Liquid Microextraction Prior to Gas Chromatography-Mass Spectrometry - Xiaojun Zhang; Xiaoguo Ma; Xin Li; Chunying Li; Rui Wang; Meiqin Chen (Water, Air, & Soil Pollution, 2018)

Genome-wide analysis and identification of the SMXL gene family in apple (Malus × domestica) - Rui Li; Jian-Ping An; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Tree Genetics & Genomes, 2018)

Association Between Body Mass Index and Disease Severity in Chinese Spinocerebellar Ataxia Type 3 Patients - Jin-Shan Yang; Ping-Ping Chen; Min-Ting Lin; Mei-Zhen Qian; Hui-Xia Lin; Xiao-Ping Chen; Xian-Jin Shang; Dan-Ni Wang; Yu-Chao Chen; Bin Jiang; Yi-Jun Chen; Ning Wang; et al. (The Cerebellum, 2018)

Evolution, functional differentiation, and co-expression of the RLK gene family revealed in Jilin ginseng, Panax ginseng C.A. Meyer - Yanping Lin; Kangyu Wang; Xiangyu Li; Chunyu Sun; Rui Yin; Yanfang Wang; Yi Wang; Meiping Zhang (Molecular Genetics and Genomics, 2018)

Design, synthesis, and biological evaluation of Cyclobentinib (CB1107) as a potential anti-CML agent - Zijun Zhou; Yang Wang; Jun Li; Baichun Hu; Xiaolin Lin; Ye Chen; Rui Wang; Ju Liu; Hongsheng Liu (Medicinal Chemistry Research, 2018)

AFLP analysis revealed a north to south genetic break in the brown alga Sargassum thunbergii along the coast of China - Juan Liu; Dongmei Zhan; Rui Zhang; Lu Zeng; Gaoge Wang; Zi-Min Hu (Journal of Applied Phycology, 2018)

Low dosage of arsenic trioxide (As2O3) inhibits angiogenesis in epithelial ovarian cancer without cell apoptosis - Dehong Luo; Xiaoyuan Zhang; Renle Du; Wenjuan Gao; Na Luo; Shuangtao Zhao; Yi Li; Rui Chen; Hui Wang; Yonghua Bao; Wancai Yang; Daishun Liu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Preface: Groundwater sustainability in fast-developing China - Yanxin Wang; Rui Ma; Wenke Wang; Xiaosi Su (Hydrogeology Journal, 2018)

Review: Safe and sustainable groundwater supply in China - Yanxin Wang; Chunmiao Zheng; Rui Ma (Hydrogeology Journal, 2018)

Assessing the influence of climate change and inter-basin water diversion on Haihe River basin, eastern China: a coupled model approach - Jun Xia; Qiang Wang; Xiang Zhang; Rui Wang; Dunxian She (Hydrogeology Journal, 2018)

Groundwater sustainability and groundwater/surface-water interaction in arid Dunhuang Basin, northwest China - Jingjing Lin; Rui Ma; Yalu Hu; Ziyong Sun; Yanxin Wang; Colin P. R. McCarter (Hydrogeology Journal, 2018)

Association analysis between spatiotemporal variation of vegetation greenness and precipitation/temperature in the Yangtze River Basin (China) - Lifang Cui; Lunche Wang; Ramesh P. Singh; Zhongping Lai; Liangliang Jiang; Rui Yao (Environmental Science and Pollution Research, 2018)

Petrogenesis and Ore Genesis of the Late Yanshanian Granites and Associated Porphyry-Skarn W-Mo Deposits from the Yunkai Area of South China: Evidence from the Zircon U-Pb Ages, Hf Isotopes and Sulfide S-Fe Isotopes - Xinyu Wang; Zhen Yang; Nengsong Chen; Rui Liu (Journal of Earth Science, 2018)

Temporal and Spatial Variations of Microbial Carbon Utilization in Water Bodies from the Dajiuhu Peatland, Central China - Rui-Cheng Wang; Hong-Mei Wang; Xing Xiang; Yu Gao; Qing-Wei Song; Lin-Feng Gong (Journal of Earth Science, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Spatial distance and climate determine modularity in a cross‐biomes plant–hummingbird interaction network in Brazil - Andréa Cardoso Araujo; Ana M. Martín González; Brody Sandel; Pietro K. Maruyama; Erich Fischer; Jeferson Vizentin‐Bugoni; Francielle Paulina de Araújo; Aline Góes Coelho; Rogério Rodrigues Faria; Glauco Kohler; Flor Maria Guedes Las‐Casas; Ariadna Valentina Lopes; et al. (Journal of Biogeography, 2018)
Aim We examined the effects of space, climate, phylogeny and species traits on module composition in a cross‐biomes plant–hummingbird network. Location Brazil, except Amazonian region. Methods We compiled 31 local binary plant–hummingbird networks, combining them into one cross‐biomes metanetwork. We conducted a modularity analysis and tested the relationship between species’ module membership with traits, geographical location, climatic conditions and range sizes, employing random forest models. We fitted reduced models containing groups of related variables (climatic, spatial, phylogenetic, traits) and combinations of groups to partition the variance explained by these sets into unique and shared components. Results The Brazilian cross‐biomes network was composed of 479 plant and 42 hummingbird species, and showed significant modularity. The resulting six modules conformed well to vegetation domains. Only plant traits, not hummingbird traits, differed between modules, notably plants’ growth form, corolla length, flower shape and colour. Some modules included plant species with very restricted distributions, whereas others encompassed more widespread ones. Widespread hummingbirds were the most connected, both within and between modules, whereas widespread plants were the most connected between modules. Among traits, only nectar concentration had a weak effect on among‐module connectivity. Main conclusions Climate and spatial filters were the main determinants of module composition for hummingbirds and plants, potentially related to resource seasonality, especially for hummingbirds. Historical dispersal‐linked contingency, or environmental variations not accounted for by the explanatory factors here evaluated, could also contribute to the spatial component. Phylogeny and morphological traits had no unique effects on the assignment of species to modules. Widespread species showed higher within‐ and/or among‐module connectivity, indicating their key role connecting biomes, and, in the case of hummingbirds, communities within biomes. Our results indicate that biogeography and climate not only determine the variation of modularity in local plant–animal networks, as previously shown, but also affect the cross‐biomes network structure.

Novel phage–host interactions and evolution as revealed by a cyanomyovirus isolated from an estuarine environment - Yongle Xu; Rui Zhang; Nannan Wang; Lanlan Cai; Yigang Tong; Qiang Sun; Feng Chen; Nianzhi Jiao (Environmental Microbiology, 2018)
Summary Cyanophages are thought to affect the community structure, population dynamics, metabolic activity and evolution of picocyanobacteria and to impact the biogeochemical cycling in aquatic ecosystems. Here, we report an estuarine Synechococcus phage, S‐CBWM1, which represents a novel viral lineage and exhibits interesting genetic features related to phage–host interactions and evolution. S‐CBWM1 encapsidates four virion‐associated proteins related to cellular metabolic regulation. Several novel auxiliary metabolic genes related to multidrug efflux, cell wall and capsule synthesis or modifications were also identified. In addition, the presence of the largest number of tRNA genes hitherto found in a phage genome may contribute to the translation efficiency of unique genes. These genomic and proteomic features of S‐CBWM1 suggested phage–host interactions involved in adaptation to eutrophic estuarine environments. Phylogenetic and metagenomic analysis of the pol γ gene in the S‐CBWM1 genome provided new insights into the evolutionary path of mitochondrial DNA polymerase gamma. The S‐CBWM1 psbA contains two group I introns, representing the first instance of multiple introns within psbA from phage. The isolation of S‐CBWM1 reveals that estuarine ecosystems contain evolutionarily novel cyanophages that drive unique phage–host interactions.

A new 12,17-cyclo-labdane diterpenoid from the twigs of Dacrycarpus imbricatus - Zuofa Yang; Qiuxiang Wang; Wei Peng; Rui Zhan; Yegao Chen (Natural Product Research, 2018)

Use of Monte Carlo simulation to evaluate the efficacy of tigecycline and minocycline for the treatment of pneumonia due to carbapenemase-producing Klebsiella pneumoniae - Wentao Ni; Guobao Li; Jin Zhao; Junchang Cui; Rui Wang; Zhancheng Gao; Youning Liu (Infectious Diseases, 2018)

Impact of Land Use Change on Hydrologic Processes in a Large Plain Irrigation District - Xiao-Bo Luan; Pu-Te Wu; Shi-Kun Sun; Xiao-Lei Li; Yu-Bao Wang; Xue-Rui Gao (Water Resources Management, 2018)

Fine mapping and identification of a novel locus qGL12.2 control grain length in wild rice (Oryza rufipogon Griff.) - Lan Qi; Yingbin Ding; Xiaoming Zheng; Rui Xu; Lizhen Zhang; Yanyan Wang; Xiaoning Wang; Lifang Zhang; Yunlian Cheng; Weihua Qiao; Qingwen Yang (Theoretical and Applied Genetics, 2018)

The gene conferring susceptibility to spot blotch caused by Cochliobolus sativus is located at the Mla locus in barley cultivar Bowman - Yueqiang Leng; Mingxia Zhao; Rui Wang; Brian J. Steffenson; Robert S. Brueggeman; Shaobin Zhong (Theoretical and Applied Genetics, 2018)

Retention of silver nanoparticles and silver ion to natural soils: effects of soil physicochemical properties - Rui Wang; Huan Du; Yujun Wang; Dengjun Wang; Qian Sun; Dongmei Zhou (Journal of Soils and Sediments, 2018)

Hydrochemical characteristics and quality assessment of groundwater for irrigation use in central and eastern Songnen Plain, Northeast China - Jianmin Bian; Siyu Nie; Rui Wang; Hanli Wan; Caihong Liu (Environmental Monitoring and Assessment, 2018)

Effects of Fluoride on SOD and CAT in Testis and Epididymis of Mice - Zilong Sun; Sujuan Li; Zhenzhen Guo; Rui Li; Jixiang Wang; Ruiyan Niu; Jundong Wang (Biological Trace Element Research, 2018)

Ancylomarina psychrotolerans sp. nov., isolated from sediments of Fildes Peninsula and emended the description of genus Ancylomarina - Chao Jia; Hong-chang Cui; Yan-qiong Han; Tian-yu Fu; Rui Du; Xiao-lei Wang; Xiao-chong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2018)

De novo RNA-seq and functional annotation of Ornithonyssus bacoti - DongLing Niu; RuiLing Wang; YaE Zhao; Rui Yang; Li Hu (Experimental and Applied Acarology, 2018)

Transformations of 2-line ferrihydrite and its effect on cadmium adsorption - Yi Huang; Shipeng Zhang; Chao Liu; Huilin Lu; Shijun Ni; Xin Cheng; Zhijie Long; Rui Wang (Environmental Science and Pollution Research, 2018)

Low-level concentrations of aminoglycoside antibiotics induce the aggregation of cyanobacteria - Lin-Rui Tan; Peng-Fei Xia; Raymond J. Zeng; Qian Li; Xue-Fei Sun; Shu-Guang Wang (Environmental Science and Pollution Research, 2018)

Modeling impacts of climate change on the geographic distribution of medicinal plant Fritillaria cirrhosa D. Don - Qi Zhao; Rui Li; Yingying Gao; Qian Yao; Xiaoqiang Guo; Wenguo Wang (Plant Biosystems, 2018)

Assessing non-linear variation of temperature and precipitation for different growth periods of maize and their impacts on phenology in the Midwest of Jilin Province, China - Enliang Guo; Jiquan Zhang; Yongfang Wang; Si Alu; Rui Wang; Danjun Li; Si Ha (Theoretical and Applied Climatology, 2018)

Cryobiotechnology of apple (Malus spp.): development, progress and future prospects - Min-Rui Wang; Long Chen; Jaime A. Teixeira da Silva; Gayle M. Volk; Qiao-Chun Wang (Plant Cell Reports, 2018)

Repetitive transcranial magnetic stimulation inhibits Sirt1/MAO-A signaling in the prefrontal cortex in a rat model of depression and cortex-derived astrocytes - Zheng-wu Peng; Fen Xue; Cui-hong Zhou; Rui-guo Zhang; Ying Wang; Ling Liu; Han-fei Sang; Hua-ning Wang; Qing-rong Tan (Molecular and Cellular Biochemistry, 2018)

Potentiation effects by usnic acid in combination with antibiotics on clinical multi-drug resistant isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Guo-Ying Zuo; Rui-Chun Fu; Wei Yu; Yun-Ling Zhang; Gen-Chun Wang (Medicinal Chemistry Research, 2018)

Joint inversion of GNSS and teleseismic data for the rupture process of the 2017 Mw6.5 Jiuzhaigou, China, earthquake - Qi Li; Kai Tan; Dong Zhen Wang; Bin Zhao; Rui Zhang; Yu Li; Yu Jie Qi (Journal of Seismology, 2018)

A novel 76-mer peptide mimic with the synergism of superoxide dismutase and glutathione peroxidase - Yawei Xu; Yan Zhou; Rui Yin; Cheng Wang; Haijiao Chu; Junling Wang (In Vitro Cellular & Developmental Biology - Animal, 2018)

Characteristics and health risk assessment of volatile organic compounds emitted from interior materials in vehicles: a case study from Nanjing, China - Liqun Xing; Lichao Wang; Rui Zhang (Environmental Science and Pollution Research, 2018)

A novel bispecific antibody fusion protein co-targeting EGFR and CD47 with enhanced therapeutic index - Yun Yang; Rui Guo; Qi Chen; Youxun Liu; Pengfei Zhang; Ziheng Zhang; Xi Chen; Tianyun Wang (Biotechnology Letters, 2018)

Alleviation of Arsenic-Induced Pulmonary Oxidative Damage by GSPE as Shown during In vivo and In vitro Experiments - Meng Wei; Fangming Guo; Dongsheng Rui; Haixia Wang; Gangling Feng; Shugang Li; Guanling Song (Biological Trace Element Research, 2018)

Dietary exposure to cadmium of Shenzhen adult residents from a total diet study - Zhou Wang; Liubo Pan; Guihua Liu; Huimin Zhang; Jinzhou Zhang; Jie Jiang; Ying Xiao; Weibin Bai; Rui Jiao; Wei Huang (Food Additives & Contaminants: Part A, 2018)

Hi1a as a Novel Neuroprotective Agent for Ischemic Stroke by Inhibition of Acid-Sensing Ion Channel 1a - Yandong Ren; Chengchong Li; Jinlong Chang; Rui Wang; Yuhua Wang; Xiang-Ping Chu (Translational Stroke Research, 2018)

Enhanced drought tolerance in tomato plants by overexpression of SlMAPK1 - Liu Wang; Ruirui Zhao; Rui Li; Wenqing Yu; Meijing Yang; Jiping Sheng; Lin Shen (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Atg7-Mediated Autophagy Is Involved in the Neural Crest Cell Generation in Chick Embryo - Guang Wang; En-ni Chen; Chang Liang; Jianxin Liang; Lin-rui Gao; Manli Chuai; Andrea Münsterberg; Yongping Bao; Liu Cao; Xuesong Yang (Molecular Neurobiology, 2018)

Comparative growth increments of gladius surface and cross-sections to estimate Sthenoteuthis oualaniensis age - Xue Feng Wang; Bi Lin Liu; Jian Hua Li; Rui Jiang; Jing Yuan Lin; Teng Li (Marine Biology, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Mechanism of salt-induced activity enhancement of a marine-derived laccase, Lac15 - Jie Li; Yanan Xie; Rui Wang; Zemin Fang; Wei Fang; Xuecheng Zhang; Yazhong Xiao (European Biophysics Journal, 2018)

Photosynthetic response of Bangia fuscopurpurea (Bangiales, Rhodophyta) towards dehydration and hyposalinity - Wen Jun Wang; Zong Gen Shen; Xiu Tao Sun; Fu Li Liu; Zhou Rui Liang; Fei Jiu Wang; Jian Yi Zhu (Biologia, 2018)

Porosity model and air leakage flow field simulation of goaf based on DEM-CFD - Gang Wang; Hao Xu; Mengmeng Wu; Yue Wang; Rui Wang; Xiaoqiang Zhang (Arabian Journal of Geosciences, 2018)

U–Pb zircon, geochemical and Sr–Nd–Hf isotopic constraints on age and origin of the intrusions from Wunugetushan porphyry deposit, Northeast China: implication for Triassic–Jurassic Cu–Mo mineralization in Mongolia–Erguna metallogenic belt - Kui-Feng Mi; Zhen-Jiang Liu; Rui-Bin Liu; Chun-Feng Li; Jian-Ping Wang; Run-Min Peng (International Geology Review, 2018)

The adaptability of a wetland plant species Myriophyllum aquaticum to different nitrogen forms and nitrogen removal efficiency in constructed wetlands - Rui Wang; Na Bai; Shengjun Xu; Guoqiang Zhuang; Zhihui Bai; Zhirui Zhao; Xuliang Zhuang (Environmental Science and Pollution Research, 2018)

A study on the role that quorum sensing play in antibiotic-resistant plasmid conjugative transfer in Escherichia coli - Yueheng Zhang; Qingping Ma; Bingmei Su; Rui Chen; Juan Lin; Zhifen Lin; Dali Wang; Yang Yu (Ecotoxicology, 2018)

Response of soil physical and chemical properties to Rocky desertification succession in South China Karst - Maoyin Sheng; Kangning Xiong; Linjiao Wang; Xiaona Li; Rui Li; Xingjun Tian (Carbonates and Evaporites, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Cryobiotechnology of forest trees: recent advances and future prospects - Jing-Wei Li; Elif Aylin Ozudogru; Jiao Li; Min-Rui Wang; Wen-Lu Bi; Maurizio Lambardi; Qiao-Chun Wang (Biodiversity and Conservation, 2018)

Acoustic parameters inversion and sediment properties in the Yellow River reservoir - Chang-Zheng Li; Yong Yang; Rui Wang; Xiao-Fei Yan (Applied Geophysics, 2018)

Algebraic encoding scheme for aperture 3 hexagonal discrete global grid system - Jin Ben; YaLu Li; ChengHu Zhou; Rui Wang; LingYu Du (Science China Earth Sciences, 2018)

CD137–CD137L interaction modulates neointima formation and the phenotype transformation of vascular smooth muscle cells via NFATc1 signaling - Wei Zhong; Bo Li; Ping Yang; Rui Chen; Cuiping Wang; Zhongqun Wang; Chen Shao; Wei Yuan; Jinchuan Yan (Molecular and Cellular Biochemistry, 2018)

Periodical drying or no drying during aquaculture affects the desiccation tolerance of a sublittoral Pyropia yezoensis strain - Xiao-lei Li; Wen-jun Wang; Fu-li Liu; Zhou-rui Liang; Xiu-tao Sun; Hai-qing Yao; Fei-jiu Wang (Journal of Applied Phycology, 2018)

Enhanced phosphorus removal using acid-treated magnesium slag particles - Xianqiang Tang; Rui Li; Min Wu; Lei Dong; Zhenhua Wang (Environmental Science and Pollution Research, 2018)

Genomic analysis of a recombinant NADC30-like porcine reproductive and respiratory syndrome virus in china - Lin-jian Wang; Bo Wan; Zhenhua Guo; Songlin Qiao; Rui Li; Sha Xie; Xin-xin Chen; Gaiping Zhang (Virus Genes, 2018)

A new cinnamic acid glycoside from roots of Heracleum dissectum - Zhi-Gang Wang; Jie Mi; Xin-Rui Wang; Ya-Yu Huo; Ya-Jie Peng; Hai-Min Zhang; Yang Gao; Hai-Long Zhang (Natural Product Research, 2018)

Three new polyketides from the marine sponge-derived fungus Trichoderma sp. SCSIO41004 - Xiaoyan Pang; Xiuping Lin; Yongqi Tian; Rui Liang; Junfeng Wang; Bin Yang; Xuefeng Zhou; Kumaravel Kaliyaperumal; Xiaowei Luo; Zhengchao Tu; Yonghong Liu (Natural Product Research, 2018)

Geochemistry and Sr–Nd isotope composition of Carboniferous volcanic rocks of the Jueluotage Orogenic Belt: implications for the tectonic evolution of Eastern Tianshan, China - Cao Rui; Muhetaer Zari; Nijat Abdursul; Cai hongming; Wang Dunke (International Geology Review, 2018)

A single nucleotide mutation of IspF gene involved in the MEP pathway for isoprenoid biosynthesis causes yellow-green leaf phenotype in rice - Rui Huang; Yang Wang; Pingrong Wang; Chunmei Li; Fuliang Xiao; Nenggang Chen; Na Li; Caixia Li; Changhui Sun; Lihua Li; Rongjun Chen; Zhengjun Xu; et al. (Plant Molecular Biology, 2018)

Precipitation drives the biogeographic distribution of soil fungal community in Inner Mongolian temperate grasslands - Di Wang; Yichao Rui; Kai Ding; Xiaoyong Cui; Yanbin Hao; Li Tang; Zhe Pang; Biao Zhang; Shutong Zhou; Kui Wang; Yanfen Wang (Journal of Soils and Sediments, 2018)

A Fluorescent Sensor of 3-Aminobenzeneboronic Acid Functionalized Hydrothermal Carbon Spheres for Facility Detection of L-tryptophan - Rui Zhang; Li-Xia Wang; Yun-Di Zhang; Chun-Hua Ge; Jia-Ping Wang; Ying Zhang; Xiang-Dong Zhang (Journal of Fluorescence, 2018)

Spatial trends and pollution assessment for mercury in the surface soils of the Nansi Lake catchment, China - Ming-Yi Ren; Li-Yuan Yang; Long-Feng Wang; Xue-mei Han; Jie-Rui Dai; Xu-Gui Pang (Environmental Science and Pollution Research, 2018)

Association between coal consumption and urbanization in a coal-based region: a multivariate path analysis - Xiaojia Guo; Zilong Zhang; Rui Zhao; Guokui Wang; Jing Xi (Environmental Science and Pollution Research, 2018)

Effect of nanoparticle hydroxyapatite on the immobilization of Cu and Zn in polluted soil - Rui-Juan Sun; Jie-Hua Chen; Ting-Ting Fan; Dong-Mei Zhou; Yu-Jun Wang (Environmental Science and Pollution Research, 2018)

Improvement of uridine production in Bacillus subtilis by metabolic engineering - Yanhong Wang; Ranjing Ma; Lu Liu; Lin He; Rui Ban (Biotechnology Letters, 2018)